CagA+Helicobacter pylori infection and N‐nitrosodimethylamine administration induce cholangiocarcinoma development in hamsters. Issue 4 (24th May 2021) - Dangtakot, Rungtiwa; Intuyod, Kitti; Chamgramol, Yaovalux; Pairojkul, Chawalit; Pinlaor, Somchai; Jantawong, Chanakan; Pongking, Thatsanapong; Haonon, Ornuma; Ma, Ning; Pinlaor, Porntip
Abstract: Background: Helicobacter pylori (HP) has been detected in the hepatobiliary tract of cholangiocarcinoma (CCA) patients in regions both endemic and non‐endemic for Opisthorchis viverrini (OV) infection. However, whether H . pylori infection promotes CCA development remains unknown. We investigated CCA development in hamsters induced by a combination of infection with H . pylori and administration of N ‐nitrosodimethylamine (NDMA) and compared findings with those in an OV plus NDMA group. Materials and Methods: Eighty‐five hamsters were divided into four groups: (1) normal, (2) administered NDMA, (3) infected with cagA + H . pylori and administered NDMA (HN group), and (4) infected with OV and administered NDMA (ON group). Animals were euthanized at 3 and 6 months post‐infection. Histopathological changes of liver and the expression of markers associated with carcinogenesis were studied. Results: At 3 months post‐infection (p.i.), cholangitis and lymphoid follicles without tumor appearance were noted in the HN group, whereas extensive fibrosis was seen in members of the ON group, 10% of which had developed tumors. At 6 months p.i., 10% of hamsters administered NDMA alone had developed CCA, whereas in the HN and ON groups, 20% and 60% of hamsters, respectively, had developed CCA. Cytokeratin‐19 (CK19) expression was observed in the CCA tissues of both the HN and the ON groups, confirming the bile duct origin of the CCA cells. CCA development in the HN group might be inflammation‐mediated, as suggested by overexpression of HMGB1, PCNA, IL ‐ 8, and 8‐OxodG in CCA tissues. Conclusion: cagA + H . pylori infection and carcinogen intake can induce CCA development with slow progression.